Behavioural aspects of risk management in Polish enterprises based on surveys’ results - Jonek-Kowalska, Izabela (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
The main purpose of the article is to identify and characterize behavioural factors in risk management in Polish enterprises based on surveys carried out on a randomly selected research sample (722 medium and large enterprises) in 2019. The risk perception, risk appetite and risk attitudes characterizing the managers of the surveyed enterprises are successively analysed. Research shows that Polish medium and large enterprises perceived risk mainly as a threat. They are also characterized by a high declarative risk appetite, which is not directly reflected in risk attitudes (high domination of risk avoidance).